Teachers’ readiness to create the inclusive and computer-orientated environment at primary school - Chupakhina, Svitlana (ScienceRise: Pedagogical Education, 2020)
The article deals with peculiarities of training specialists to create the inclusive and computer-oriented educational environment. A number of structural components that take a crucial system-forming role are highlighted in the article, namely a system of basic and professional future teachers’ values in inclusive education, practical potential, resource support for correctional and development activities and professional skills in the field of information and communication technologies and willingness to participate in e-education. Research methods: psychological and pedagogical experiment, providing the qualitative and quantitative analysis of results, observations, questionnaires, interviews, modeling method and mathematical statistics. The aim of the research work is to substantiate the structure and content of the inclusive and computer-orientated educational environment that will identify priority areas and activities in educational establishments and trace the range of professional competencies as a basis for working out a special course on syllabus. The research work was carried out. It dealt with process of training future teachers to use electronic educational resources in the inclusive environment (to work in a team, implementing a comprehensive approach to educate a child with special educational needs, as well as to carry out diagnostic-advisory and pedagogical support). All mentioned above involved the students in studying the educational discipline. Research findings on training future teachers to work in the inclusive educational and computer-orientated environment indicate that the competencies that are formed are rather satisfying, but there are certain aspects that teachers need to focus on, these are information and communication technology opportunities, they can use at work